2003
DOI: 10.1523/jneurosci.23-08-03221.2003
|View full text |Cite
|
Sign up to set email alerts
|

Focal Lysolecithin-Induced Demyelination of Peripheral Afferents Results in Neuropathic Pain Behavior That Is Attenuated by Cannabinoids

Abstract: Demyelinating diseases can be associated with painful sensory phenomena such as tactile allodynia and hyperalgesia. To study the mechanisms underlying demyelination-induced pain, we have characterized a novel model of demyelination of the sciatic or saphenous nerve. Topical lysolecithin application causes focal demyelination of afferent nerve A-fibers without axonal loss, as assessed either by electron and light microscopy or by immunohistochemical analysis of dorsal root ganglia (DRG) for a neuronal injury ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 95 publications
9
96
0
Order By: Relevance
“…In particular, the myelin degradation of A␤ afferents promotes susceptibility of their axonal plasma membrane to pronociceptive stimuli, leading to ectopic depolarization and mechanical allodynia (Kobayashi et al, 2008). Accordingly, neuropathic pain behaviors occurred after experimental demyelination of peripheral or central neurons (Wallace et al, 2003;Inoue et al, 2004;Moalem-Taylor et al, 2007;Zhu et al, 2012) and in mutant mice with aberrant myelination or loss of myelin (Gillespie et al, 2000;Chen et al, 2006). Moreover, neuropathic pain accompanies many demyelinating human diseases, such as Guillain-Barré syndrome, CharcotMarie-Tooth type I disease, and multiple sclerosis (Ueda, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the myelin degradation of A␤ afferents promotes susceptibility of their axonal plasma membrane to pronociceptive stimuli, leading to ectopic depolarization and mechanical allodynia (Kobayashi et al, 2008). Accordingly, neuropathic pain behaviors occurred after experimental demyelination of peripheral or central neurons (Wallace et al, 2003;Inoue et al, 2004;Moalem-Taylor et al, 2007;Zhu et al, 2012) and in mutant mice with aberrant myelination or loss of myelin (Gillespie et al, 2000;Chen et al, 2006). Moreover, neuropathic pain accompanies many demyelinating human diseases, such as Guillain-Barré syndrome, CharcotMarie-Tooth type I disease, and multiple sclerosis (Ueda, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that a disruption of myelin sheath integrity of peripheral nerves might be involved, because previous work demonstrated that (1) the myelin sheath is highly susceptible to degeneration caused by H 2 O 2 (Konat and Wiggins, 1985;Richter-Landsberg and Vollgraf, 1998;Laszkiewicz et al, 1999;Mronga et al, 2004;Perfeito et al, 2007), (2) the myelin sheath is disrupted and the proximal nerve stump seals off after peripheral nerve injury (Inoue et al, 2004;Devor, 2006a;Nagai et al, 2010), and (3) the dysmyelination of peripheral nerves induced by nerve injury or by delivery of bioactive lipids, such as lysophosphatidic acid, is accompanied by spontaneous action potentials in primary afferent nerves and sensitization of sensory processing, thereby contributing to neuropathic pain hypersensitivity (Devor et al, 1989;Wallace et al, 2003;Devor, 2006b;Ueda, 2008;Zhu et al, 2012). To monitor the time course of injury-induced dysmyelination of peripheral nerves in the SNI model, we first analyzed the protein levels of MPZ, the main peripheral myelin protein, in C57BL/6 mice during 21 d after SNI.…”
Section: Sni-induced Dysmyelination Of Peripheral Nerves Is Reduced Imentioning
confidence: 99%
“…The majority (82.9%) of CRP2 mRNA-positive neurons were positive for peripherin (Fig. 4 D-F ), which labels the small-diameter, unmyelinated C-fiber DRG cell population (Wallace et al, 2003). Only a small portion (7.8%) of CRP2 mRNA-positive neurons expressed NF200 (clone N52), a marker of large-diameter, myelinated DRG neurons (Fig.…”
Section: Crp2 Mrna Expression In Drgsmentioning
confidence: 97%
“…Alternatively, whereas demyelination in the CNS results in upregulation of Nav1.2, demyelination in the PNS might result in upregulation of Nav1.8 or another Nav channel. For example, Wallace et al (2003) showed that lysolecithinmediated demyelination upregulates Nav1.3 channel expression in DRG neurons. It is not known whether this Nav1.3 is transported into axons and/or localizes to specific membrane domains (e.g.…”
Section: Role Of Myelination In Nav Channel Subtype Switchingmentioning
confidence: 99%